1990
DOI: 10.1161/01.res.67.6.1334
|View full text |Cite
|
Sign up to set email alerts
|

Regional changes in creatine kinase and myocyte size in hypertensive and nonhypertensive cardiac hypertrophy.

Abstract: Several intracellular enzymes have been shown to have altered total activity or isoenzyme composition in cardiac hypertrophy. This study tests the hypothesis that the accumulation of the fetal-type (BB + MB) creatine kinase (CK) isoenzymes in hypertrophied adult myocardium is related to an increase in blood pressure. Consideration was made for the location, size, and hemodynamic load of the myocytes. By using the two-kidney, one-clip (2K1C) rat model of renal hypertension with and without hydralazine treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 33 publications
3
45
1
Order By: Relevance
“…It is notable that the septal artery is derived from a superficial portion of the right ventricular side of the septal wall, whereas, in the present study, vessels were obtained from within the left ventricular free wall. Previous studies have demonstrated increased glycolytic activity in left ventricle vs. septal tissue samples from bovine and rat hearts (36,42). Therefore, it is possible that differences in metabolic demand of these vascular beds may contribute to the variant findings.…”
Section: Discussionmentioning
confidence: 94%
“…It is notable that the septal artery is derived from a superficial portion of the right ventricular side of the septal wall, whereas, in the present study, vessels were obtained from within the left ventricular free wall. Previous studies have demonstrated increased glycolytic activity in left ventricle vs. septal tissue samples from bovine and rat hearts (36,42). Therefore, it is possible that differences in metabolic demand of these vascular beds may contribute to the variant findings.…”
Section: Discussionmentioning
confidence: 94%
“…This is wellillustrated by an early study in which cell size and enzyme activities of several proteins known to change in cardiac hypertrophy and failure were measured in myocytes isolated from different regions of hypertensive and nonhypertensive hypertrophied rat hearts (2 kidney, 1 clip model). 57 Some proteins increased in proportion to myocyte size while others were relatively diluted, and still others increased out of proportion to myocyte size. Regulation of gene expression differed among neighboring cells within the same organ.…”
Section: On the Causes Of Altered Energetic Phenotypementioning
confidence: 97%
“…Specific cytosolic and mitochondrial isoforms of CK maintain high ATP/ADP ratios at the myofibrillar sites of utilization and low ATP/ADP ratios at the mitochondrial sites of production. The CK cytosolic isozyme shift to more "fetal" isoforms in LVH models 7,14,15 and in human LVH 4 is postulated to offer a thermodynamic advantage. CK isoform analysis could not be performed in the present noninvasive study of stable ambulatory patients with LVH because there was no clinical indication for the requisite cardiac biopsy.…”
Section: Myocardial High-energy Phosphate Metabolism and The Role Of Ckmentioning
confidence: 99%
“…4,5 The PCr/ATP ratio is one indicator of the energetic state of the myocardium and is reduced in animal models of myocardial hypertrophy, 6,7 in human LVH, 8 -10 and in CHF. 11,12 Despite the potential importance of the cardiac PCr/ATP ratio for understanding cardiac energetics, this ratio does not directly reflect the rate of ATP production through the CK reaction, 7,[13][14][15] which may be more important in the progression to CHF in patients with LVH.…”
mentioning
confidence: 99%